Diurnal Post-Activation Performance Enhancement (PAPE) - Effect of resistance priming in college badminton players - Sudhakaran, S. C.; Dada, T.; Rajan, R.; Shafi, M.; Nisar, N. N. S. (Polish Journal of Sport and Tourism, 2025)
Introduction. Badminton is characterized by intermittent power actions including high-intensity jumps, turns, strikes and lunges. Power, maximal strength, agility and speed endurance are of paramount importance for varied formats of badminton. Resistance priming (RP) aids in attaining post-activation performance enhancement (PAPE) in muscular activities. The study was aimed at examining the potential effect of resistance priming exercise on improving anaerobic variables in college badminton players measured at various time points.